KOtBu‐Catalyzed Michael Addition Reactions Under Mild and Solvent‐Free Conditions. Issue 4 (20th January 2020) - Thiyagarajan, Subramanian; Krishnakumar, Varadhan; Gunanathan, Chidambaram
Abstract: Designed transition metal complexes predominantly catalyze Michael addition reactions. Inorganic and organic base‐catalyzed Michael addition reactions have been reported. However, known base‐catalyzed reactions suffer from the requirement of solvents, additives, high pressure and also side‐reactions. Herein, we demonstrate a mild and environmentally friendly strategy of readily available KO t Bu‐catalyzed Michael addition reactions. This simple inorganic base efficiently catalyzes the Michael addition of underexplored acrylonitriles, esters and amides with (oxa‐, aza‐, and thia‐) heteroatom nucleophiles. This catalytic process proceeds under solvent‐free conditions and at room temperature. Notably, this protocol offers an easy operational procedure, broad substrate scope with excellent selectivity, reaction scalability and excellent TON (>9900). Preliminary mechanistic studies revealed that the reaction follows an ionic mechanism. Formal synthesis of promazine is demonstrated using this catalytic protocol. Abstract : Touching base : A mild and environmentally friendly strategy of a readily available base‐KO t Bu catalyzed Michael addition reaction is demonstrated. Notably, this catalytic process proceeds under solvent‐free conditions at room temperature, and offers an easy operational procedure, broad substrate scope with excellent selectivity, reaction scalability and excellent TON (>9900).